2003
DOI: 10.1002/em.10174
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific mutagenicity of stereochemically defined 1,N2‐deoxyguanosine adducts of trans‐4‐hydroxynonenal in mammalian cells

Abstract: Trans-4-hydroxynonenal (HNE) is a toxic compound produced endogenously during lipid peroxidation. HNE is a potent electrophile that is reactive with both proteins and nucleic acids. HNE preferentially reacts with deoxyguanosine to form four stereoisomeric HNE-deoxyguanosine (HNE-dG) adducts: (6R, 8S, 11R), (6S, 8R, 11S), (6R, 8S, 11S), and (6S, 8R, 11R). These adducts were synthesized into 12-mer oligodeoxynucleotides, inserted into a DNA shuttle vector and evaluated for the ability of each stereoisomer to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 35 publications
4
57
1
Order By: Relevance
“…The observation of a more proficient extension by Pol from a C opposite the 11R isomer than from a C opposite the 11S isomer may be because of the greater prevalence of the ring-open configuration in the 11R isomer than the 11S isomer, and that could also account for Pol's ability to extend from a C opposite the 11R isomer. The assumption that ring opening is somewhat more efficient for the 11R isomer is in a good agreement with two observations from other studies: (i) melting experiments showed that a duplex oligodeoxynucleotide containing the 11S HNE-dG is significantly more destabilized than the 11R-containing duplex (25) and (ii) whereas the 11R isomer was essentially nonmutagenic in COS-7 cells, the 11S adduct yielded approximately 4% mutations (6).…”
Section: Discussionsupporting
confidence: 90%
“…The observation of a more proficient extension by Pol from a C opposite the 11R isomer than from a C opposite the 11S isomer may be because of the greater prevalence of the ring-open configuration in the 11R isomer than the 11S isomer, and that could also account for Pol's ability to extend from a C opposite the 11R isomer. The assumption that ring opening is somewhat more efficient for the 11R isomer is in a good agreement with two observations from other studies: (i) melting experiments showed that a duplex oligodeoxynucleotide containing the 11S HNE-dG is significantly more destabilized than the 11R-containing duplex (25) and (ii) whereas the 11R isomer was essentially nonmutagenic in COS-7 cells, the 11S adduct yielded approximately 4% mutations (6).…”
Section: Discussionsupporting
confidence: 90%
“…Previously, we and other (13,14) have found that the 4-HNE-dG adduct induces mainly G:C to T:A transversions in human cells, and 4-HNE forms DNA adducts preferentially at codon 249 of p53 gene (15), a mutational hotspot in hepatocellular carcinoma and smoke-related lung cancer (16). Recently, it has been shown that 4-HNE can indeed induce a high frequency of G:C to T:A mutations at codon 249 of the p53 gene (37).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that 4-HNE can interact with DNA to form 4-HNE-dG adduct, a bulky exocyclic DNA adduct, which has been found in various normal tissues of humans and rats (1,9,12). We and others (13,14) have recently found that 4-HNE-dG adduct is a strong mutagen and induces mainly G:C to T:A mutations in human cells. We have also found that 4-HNE-dG adduct preferentially form at -GAGGC͞A-sequences in the p53 gene, including codon 249 (15), a mutational hotspot in human hepatocellular carcinoma and cigarette smokerelated lung cancer (16).…”
mentioning
confidence: 99%
“…Etheno-type adduct of HNE to guanosine, 1,N 2 ε-guanosine, and propano-type cyclic 1,N 2 -propanodeoxyguanine were shown to occur as four diastereoisomers of tetracyclic structure (purine condensed with ethano and furano rings) [40,41]. These isomers were shown to have different mutagenic potency [42]. Other cyclic DNA adducts deriving from acrolein and crotonaldehyde occur in stereomeric forms as well [43,44].…”
Section: Modification Of Dna Bases By Lpo Products and Their Processimentioning
confidence: 99%